El telar de cintura, inmanencia itinerante de la memoria - Méndez González, María Oliva (2018)
The historical testimony that emerges from the colonial texts, written by the men of the conquest, did not register the foundational role of women in society, but enunciated, tacitly and reciprocally linked, the concepts of nation and masculinity. The institutionalization of male supremacy is one of the reasons why women figure as the most deprived and violent sector of the current Central American society. As we will see in the following analysis, Mayan textile art represents a place of collective memory that resists male domination systems.